2022
DOI: 10.1007/s12033-022-00624-8
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Based Delivery Systems in Development of Genetic and Subunit Vaccines

Abstract: Lipidic carriers are composed of natural, synthetic, or physiological lipid/phospholipid materials. The flexibility of lipid-based delivery systems for transferring a variety of molecules such as immunomodulators, antigens, and drugs play a key role in design of effective vaccination and therapeutic strategies against infectious and non-infectious diseases. Genetic and subunit vaccines are two major groups of promising vaccines that have the potential for improving the protective potency against different dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 137 publications
0
5
0
Order By: Relevance
“…Therefore, recent advances in preclinical and clinical trials of lipid-based delivery systems that enhance the efficiency and safety of vaccine strategies against various diseases deserve attention. 155 …”
Section: Mechanism Of the Cellular Uptake Of Lnps And Targeting Strat...mentioning
confidence: 99%
“…Therefore, recent advances in preclinical and clinical trials of lipid-based delivery systems that enhance the efficiency and safety of vaccine strategies against various diseases deserve attention. 155 …”
Section: Mechanism Of the Cellular Uptake Of Lnps And Targeting Strat...mentioning
confidence: 99%
“…215 Helper lipids, such as dioleoyl phosphatidylethanolamine (DOPE) and 1,2-distearoyl-snglycero-3-phosphocholine (DSPC) utilized in the mRNA-1273 and BNT162b2 COVID-19 vaccines, have been observed to aid endosome escape. 216,217 The World Health Organization (WHO) proclaimed Coronavirus Infectious Disease (COVID-19) a worldwide pandemic; creating COVID-19 vaccines has become essential for the world's population, and many platforms have been researched. The FDA has authorized 12 vaccinations.…”
Section: Genetic and Subunit Vaccines In Preclinical And Clinical Tri...mentioning
confidence: 99%
“…LNP stability is maintained by PEGylated Lipids and Cholesterol, which also affect LNP biodistribution . Helper lipids, such as dioleoyl phosphatidylethanolamine (DOPE) and 1,2-distearoyl-sn-glycero-3-phosphocholine (DSPC) utilized in the mRNA-1273 and BNT162b2 COVID-19 vaccines, have been observed to aid endosome escape. , …”
Section: Genetic and Subunit Vaccines In Preclinical And Clinical Tri...mentioning
confidence: 99%
“…In comparison to liposomes, virosomes enhance the active substances from proteolytic degradation. Additionally, it is also reported that RNA vaccines are formulated using lipid nanoparticles to increase their stability and immune response (Bolhassani 2023). The most important prevention techniques highlighted based on person-to-person transmission of SARS-CoV-2 by defining the symptoms of COVID-19 patients and their host immune response towards SARS-CoV-2.…”
Section: Antiviral Nanotherapeuticsmentioning
confidence: 99%